2018
DOI: 10.1002/jcb.26763
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: MicroRNA‐183 induces epithelial‐mesenchymal transition and promotes endometrial cancer cell migration and invasion in by targeting CPEB1

Abstract: The aim of this study is to evaluate the ability of microRNA-183 (miR-183) to influence epithelial-mesenchymal transition (EMT) and cell proliferation, migration, invasion, and apoptosis in endometrial cancer (EC) by targeting cytoplasmic polyadenylation element binding protein 1(CPEB1). EC tissues with matched nonmalignant tissues were collected from 208 EC patients. Ishikawa and RL95-2 cells were selected for cell experiments in vitro and each kind of cells were grouped into blank, negative control (NC), miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…An accumulation of evidence has indicated that abnormal miRNA expression is an indication of different types of cancer, including EC (11,22,23). The dysregulation of miRNAs may serve an important role in the development and progression of EC by regulating a variety of processes, including cell proliferation, apoptosis, cycle, differentiation, metastasis and sensitivity of radiotherapy and chemotherapy (24)(25)(26). An understanding of the miRNAs associated with EC initiation and progression is crucial for the development of improved therapeutic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…An accumulation of evidence has indicated that abnormal miRNA expression is an indication of different types of cancer, including EC (11,22,23). The dysregulation of miRNAs may serve an important role in the development and progression of EC by regulating a variety of processes, including cell proliferation, apoptosis, cycle, differentiation, metastasis and sensitivity of radiotherapy and chemotherapy (24)(25)(26). An understanding of the miRNAs associated with EC initiation and progression is crucial for the development of improved therapeutic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR-182, miR-183 and miR-223 were found up-regulated in 5 articles and miR-135b was found to be up-regulated in 3 articles. MiR-182 promotes cell proliferation by targeting the tumour suppressor gene TCEAL7, miR-183 targets CPEB1 while miR-223 targets IGF-1R [56][57][58]. MiR-135b targets FOXO1 to promote cell proliferation in EC cells [59].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in hepatocellular carcinoma, CPEB1 can directly target the 3′UTR of SIRT1, control the poly (A) tail length, inhibit its translation, and negatively regulate the stemness and resistance of liver cancer [157]. In endometrial cancer, miR-183 inhibits CPEB1 expression at the transcription and translation levels, and targets CPEB1 to induce EMT and promote tumorigenesis of EC cells [158]. In addition, CPEB4, another member of the CPEB family, is highly expressed in melanoma, glioblastoma and pancreatic ductal adenocarcinoma [159,160].…”
Section: Alternative Polyadenylation (Apa)mentioning
confidence: 99%